Functionally different predators break down antipredator defenses of spider mites. Issue 1 (15th February 2014) - Otsuki, Hatsune; Yano, Shuichi
Abstract Prey that lives with functionally different predators may experience enhanced mortality risk, because of conflicts between the specific defenses against their predators. Because natural communities usually contain combinations of prey and functionally different predators, examining risk enhancement with multiple predators may help to understand prey population dynamics. It is also important in an applied context: risk enhancement with multiple biological control agents could lead to successful suppression of pests. We examined whether risk enhancement occurs in the spider mite Tetranychus kanzawai Kishida (Acari: Tetranychidae) when exposed to two predator species: a generalist ant, Pristomyrmex punctatus Mayr (Hymenoptera: Formicidae), and a specialist predatory mite, Neoseiulus womersleyi Schicha (Acari: Phytoseiidae). We replicated microcosms that consisted of spider mites, ants, and predatory mites. Spider mites avoided generalist ants by staying inside their webs on leaf surfaces. In contrast, spider mites avoided specialist predatory mites that intruded into their webs by exiting the web, which obviously conflicts with the defense against ants. In the presence of both predators, enhanced mortality of spider mites was observed. A conflict occurred between the spider mites' defenses: they seemed to move out of their webs and be preyed upon by ants. This is the first study to suggest that risk enhancement occurs in web‐spinning spider mites that are exposed to both generalist and specialist predator species, and to provide evidence that ants can have remarkable synergistic effects on the biological control of spider mites using specialist predatory mites.